Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.fm.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of five Shiga toxin-producing Escherichia coli genes with multiplex PCR

Abstract: a b s t r a c tEscherichia coli serogroup O157 is the pathogen most commonly associated with foodborne disease outbreaks, but epidemiological studies suggest that non-O157 Shiga toxin-producing E. coli (STEC) is a major player as well. The ten most clinically relevant STECs belong to serogroups O26, O103, O111, O145, O157, O91, O113, O128, O45, and O121; but emerging strains, such as O104:H4 that was identified with the 2011 German outbreak, could become more prevalent in the future. A 75-min conventional mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
(42 reference statements)
3
16
0
Order By: Relevance
“…These results agreed with (Neher et al, 2016). Different serotypes were previously reported in different studies which similar to our results O91, O78 and O2, and serotypes O113, O128, O26, O91 were previously obtained in the study carried out by ( Cordoni et al, 2016 andSon et al, 2014) respectively. On the other hand (Beutin et al, 1993) isolated O91: H-and O128: H2 from animal species.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results agreed with (Neher et al, 2016). Different serotypes were previously reported in different studies which similar to our results O91, O78 and O2, and serotypes O113, O128, O26, O91 were previously obtained in the study carried out by ( Cordoni et al, 2016 andSon et al, 2014) respectively. On the other hand (Beutin et al, 1993) isolated O91: H-and O128: H2 from animal species.…”
Section: Resultssupporting
confidence: 93%
“…The stx2 was successfully amplified in one isolate of serogroup O91. This result is similar to (Farooq et al, 2009;Son et al,2014;Yousef et al, 2015;Neher et al, 2016 andJohura et al, 2017) .…”
Section: Resultssupporting
confidence: 90%
“…Originally, the O121:H21 strain tested negative for O121 by latex agglutination, but had an amplicon similar to that of the O121 serogroup by PCR (Bai et al, 2012). As such, the strain was sent to be retested by the E. coli Reference Center (Pennsylvania State University) and subsequently identified as O113:H21; a result previously seen by Son et al (Son et al, 2014). Since antibody 12 was not directed against the LPS antigens tested in this study, we have used it as a negative antibody control.…”
Section: Western-type and Immunoblottingmentioning
confidence: 93%
“…TY-2482 (O104:H4) was obtained from Dr. John Luchansky (USDA, Agricultural Research Service, Eastern Regional Research Center, Wyndmoor, PA) and serogroup was confirmed by PCR as previously described (Paddock et al, 2013). MDCH-4 (O113:H21) was obtained from the STEC Center at Michigan State University and serogroup was confirmed by PCR according to Bai et al and subsequently retyped at the E. coli Reference Center at Pennsylvania State University (University Park, PA) (Bai et al, 2012;Son et al, 2014). Twelve separate antibodies were used for characterization studies, and the identifying numbers used throughout this paper, as well as supplier information are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This is the most variable part of the lipopolysaccharide and its serological specificity is used as one of the major bases for serotyping schemes in gram-negative bacteria (DebRoy et al 2011;Stenutz et al 2006). In the case of E. coli, 174 serogroups are currently described and some of them are considered pathogenic, such is the case of the aforementioned E. coli O142 and O91 serogroups which have been classified as enteropathogenic E. coli (EPEC) (Bugarel et al 2011) and Shiga toxing-producing E. coli (STEC) (Son et al 2014), respectively. Analogously to what is found in proteins and nucleic acids, the NH groups of amino sugars can also act as hydrogen donors and influence the three-dimensional structure of carbohydrates through inter-residue hydrogen bonding interactions (Norris et al 2012).…”
Section: Introductionmentioning
confidence: 99%